Community Meetings on the Rural Opioid Crisis: Setting a Path Forward by Learning from Others - Devon Meadowcroft; Brian Whitacre (SAGE Publishing, 2020)
Objectives: This study implemented a series of meetings in one rural community struggling with the opioid crisis. Set in the town of Ardmore, Oklahoma, these meetings presented local residents who dealt with the crisis as part of their jobs with four categories of programs aimed at preventing and treating opioid-related issues. The ultimate goal was for the participants to develop a consensus about where resources should be appropriated in the future, based off the needs of the area. Methods: Three community meetings were held over a six-week period, with an average of 40 attendees. Data was collected through surveys, study circles, and a participant voting exercise. Surveys were distributed at the beginning and end of the meetings to determine if participant views changed over the course of the study. Study circles broke participants into small groups and prompted them with questions regarding the crisis to encourage group discussion. The participant voting exercise allowed participants to note where they would like future resources to be directed. Findings: Listening to experts and holding group discussions led to changes in opinions for some participants. Most felt that the most pressing need was to provide accessible opioid treatment options in their community. Youth-based prevention efforts were also noted as being a program that the community should focus on. Conclusions: Local perceptions of the most appropriate strategies for combatting the rural opioid crisis can change with group discussions alongside others who are actively involved with this issue. Future research should actively involve affected communities in order to develop relevant and accepted action plans.